Mid-Day Meals Programs in the School of Pokhara through Child Friendly School Manual - Tripathi, Krishna Prasad (Janapriya Journal of Interdisciplinary Studies, 2023)
This study, titled “Assessing School Mid-Day Meals Programs in the Schools of Pokhara through Child-Friendly School Manual,” aimed to identify modalities and assess school facilities related to mid-day meals in both institutional and public schools. The research design employed was explanatory sequential. The population comprised schools, headmasters, and class five students, and a multistage sampling technique was utilized. Five diverse schools each from institutional (preprimary, primary, upper primary, secondary, and higher secondary) and public schools were randomly selected for comparison. During data collection, students were assured that their responses would be confidential, and teachers were not present in the classrooms to encourage free expression of opinions. The findings revealed that more than half of the students in institutional schools carried homemade lunches, while public schools provided meals in canteens. Observations indicated that insufficient seating in canteens resulted in students having to eat meals on the ground or in classrooms. Moreover, many schools lacked soap in wash bins, potentially impacting students’ hygiene, and health. It is recommended to improve school facilities related to mid-day meals in accordance with child-friendly school guidelines.